Incidence of Fusarium foot and root rot of cereals under conservation agriculture in north west Tunisia - CHEKALI, Samira; GARGOURI, Samia; BEN HAMMOUDA, Moncef; M’HAMED, Hatem Cheikh; NASRAOUI, Bouzid (Phytopathologia Mediterranea, 2019)
Conservation agriculture, based on direct drilling for crop establishment, has emerged in Tunisia since 1999/2000 as an alternative to conventional agriculture based on conventional drilling. The main objective of this approach is to ensure yield stability from crops and replenishment of soil organic matter. Previous research has demonstrated increased risks from pathogens favoured by mulching. The impacts of direct drilling on yields, and Fusarium foot and root rot of durum wheat, oat and barley, were studied over three successive growing seasons (2009/10, 2010/11, 2011/12) in northwest Tunisia. Disease incidence was estimated by the recovery frequency of Fusarium spp. isolates from stem bases and roots of plants of the three cereals. In addition, disease severity was assessed by occurrence of whiteheads that senesced prematurely, and the browning intensity on durum wheat stem bases. Grain yields were recorded at the ripening stages. Fusarium culmorum and F. pseudograminearum were isolated from the three cereals, with F. culmorum being the dominant pathogen. Direct drilling increased the incidence (60%) of these pathogens on stem bases and roots during the warmer seasons of 2009/10 and 2010/11, but less infection (37%) compared to conventional drilling was observed in the wetter season of 2011/12. Direct drilling increased the percentage of whiteheads of durum wheat (73%), but did not affect disease severity, which was estimated by the discolouration on stem bases and grain yield.